Why does the world need another rotavirus vaccine? - Richard L Ward; Monica M McNeal; A Duncan Steele (Dove Medical Press, 2008)
Richard L Ward1, Monica M McNeal1, A Duncan Steele21Division of Infectious Diseases, Cincinnati Children’s Hospital Medical Center, Cincinnati, OH, USA; 2Initiative for Vaccine Research, World Health Organization, Geneva, SwitzerlandAbstract: A “Meeting on Upstream Rotavirus Vaccines and Emerging Vaccine Producers” was held at the World Health Organization in Geneva, Switzerland on March 28–30, 2006. The purpose was to discuss, evaluate, and weigh the importance of additional rotavirus vaccine candidates following the successful international licensure of rotavirus vaccines by two major pharmaceutical companies (GlaxoSmithKline and Merck) that had been in development for many years. Both licensed vaccines are composed of live rotaviruses that are delivered orally as have been all candidate rotavirus vaccines evaluated in humans. Each is built on the experience gained with previous candidates whose development had either been discontinued or, in the case of the previously licensed rhesus rotavirus reassortant vaccine (Rotashield), was withdrawn by its manufacturer after the discovery of a rare association with intussusception. Although which alternative candidate vaccines should be supported for development and where this should be done are controversial topics, there was general agreement expressed at the Geneva meeting that further development of alternative candidates is a high priority. This development will help insure that the most safe, effective and economic vaccines are available to children in Third World nations where the vast majority of the >600,000 deaths due to rotavirus occur each year. This review is intended to provide the history and present status of rotavirus vaccines as well as a perspective on the future development of candidate vaccines as a means of promulgating plans suggested at the Geneva meeting.Keywords: rotavirus vaccines, rotavirus immunity, candidate vaccines